Emosi Pada Keluarga Broken Home Perspektif Al-Qur’an - Nurrohman, Nurrohman; Zain Sarnoto, Ahmad (Journal of Education and Islamic Studies (JEIS), 2025)
ABSTRACTThis study examines emotional intelligence in broken home families from the Qur'anic perspective, focusing on how they manage emotional struggles. Emotional intelligence based on the Qur'an is viewed as a solution for individuals experiencing trauma, depression, or engaging in social deviance such as promiscuity and crime. The research employs a qualitative library research method, analyzing Qur'anic verses alongside relevant publications, including journals and seminar proceedings. The thematic interpretation method (tafsir maudhu’i) is used to explore emotional intelligence in depth. Findings reveal that broken home individuals who apply Qur'anic emotional intelligence—especially self-awareness—develop inner control that leads to patience, gratitude, and forgiveness. They learn to face life with an open heart and remain steadfast (istiqomah) in building goodness. Compassion also emerges, helping reduce anxiety and emotional pressure. Ultimately, these values guide individuals to manage emotional turmoil with balance and resilience.. ABSTRAKPenelitian ini membahas kecerdasan emosi pada keluarga broken home dalam perspektif Al-Qur’an, khususnya bagaimana mereka mengelola pergolakan emosional. Kecerdasan emosi menurut Al-Qur’an dipandang mampu menyelesaikan masalah trauma, depresi, hingga penyimpangan sosial seperti seks bebas dan kriminalitas. Metode yang digunakan adalah kualitatif dengan pendekatan studi pustaka, menganalisis ayat-ayat Al-Qur’an dan publikasi ilmiah terkait. Penelitian ini menggunakan metode tafsir tematik (tafsir maudhu’i). Hasil menunjukkan bahwa individu dari keluarga broken home yang menerapkan kecerdasan emosi Qur’ani—khususnya aspek kesadaran diri—mampu membangun kontrol diri yang melahirkan sikap sabar, syukur, dan pemaaf. Mereka menghadapi hidup dengan kelapangan dada dan istiqomah dalam menebar kebaikan. Sikap kasih sayang turut membantu meredakan kecemasan dan tekanan batin. Nilai-nilai ini membimbing mereka untuk mengelola emosi secara seimbang dan tidak berlebihan dalam mengekspresikan gejolak emosi.